Peran Uang dalam Sistem Moneter Islam : Membangun Ekonomi yang Adil dan Stabil - Evi Silvia Aulina; Lilis Lilis; Rifda Amaliatun Nisa; Rasidah Novita Sari (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
Examining how the Islamic monetary system uses money to build a stable and just economy is the aim of this study. Money is not to be hoarded or handled like a commodity, according to the Islamic monetary system, which views it as a public good and flow notion that functions as a medium of exchange and a unit of value. In Islam, money serves primarily as a medium of exchange, a standard of payment, and a gauge of value, speculation and wealth hoarding are prohibited. In contrast to traditional interest-based systems, the Islamic monetary system places a higher priority on mechanisms that allow for profit-and-loss sharing. Because hoarding money can slow down economic turnover and produce stagnation, it is forbidden in Islam. This is because money must continue to circulate in order to preserve economic viability. QS Al-Hasyr: 7 and QS At-Taubah: 34–35, which explain hoarding of wealth and promote the use of money for the good of society, both highlight this principle of wealth sharing. Using data from pertinent literature and journals, this study employs a qualitative methodology based on literature reviews. Furthermore, This study is expected to provide the groundwork for a more effective sharia monetary policy that encourages equitable and balanced economic growth.